1997
DOI: 10.1023/a:1018587623231
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hydroxyapatite powders were prepared by a chemical precipitation method and electrophoretically deposited on Ti6Al4V surgical alloy substrates. The powders were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), particle size distribution and zeta potential measurements. Prior to electrophoretic deposition, anodic films were obtained on Ti6Al4V and studied by the Auger method. It was established that experimental conditions of powder preparation, electric field and stirring have a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(123 citation statements)
references
References 6 publications
6
116
1
Order By: Relevance
“…1c), containing individual nanofibers. This result was in a good agreement with the results of investigation into other nanomaterials [15], which indicated that stirring of nanoparticles can promote agglomeration. XRD studies (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1c), containing individual nanofibers. This result was in a good agreement with the results of investigation into other nanomaterials [15], which indicated that stirring of nanoparticles can promote agglomeration. XRD studies (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Electrophoretic deposition allows the deposition of coating from almost any material class, including metals, polymers, and ceramics (93)(94)(95)(96). The mechanism of electrophoretic deposition involves electrophoresis, in which charged particles move toward an electrode of opposite charge, and deposition, due to the motion of charged particles and their local accumulation.…”
Section: Electrophoretic Depositionmentioning
confidence: 99%
“…The mechanism of electrophoretic deposition involves electrophoresis, in which charged particles move toward an electrode of opposite charge, and deposition, due to the motion of charged particles and their local accumulation. Coating formation is achieved via particle coagulation (93)(94)(95)(96). EPD appears of particular interest in surface modifications of materials for biomedical application (48,78) because the deposition of either inorganic or hybrid coatings with high purity is possible on complex geometries.…”
Section: Electrophoretic Depositionmentioning
confidence: 99%
“…For such applications, thin films of hydroxyapatite (HAP) were prepared using an ED technique (electrophoretic deposition (EPD) [21,22] or electrolytic deposition (ELD) [23]. HAP is an established implant material because its chemical composition is similar to that of bone tissue.…”
Section: Specific Advantages Of Electrochemical Depositionmentioning
confidence: 99%